(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The article reveals the question of the prospects for the development of financial leasing in Russia against the background of modernization of the economy. The purpose of the research is to analyze the current situation of the leasing products market and assess the prospects for future development. The urgency of the issue of modernization of the economy and instruments that are applied by the state administration to stimulate the development of financial leasing are analyzed. The results of the article, in addition to the scientific community, are intended for managers of industrial enterprises and leasing companies.